Telecommunications and intra‐urban trip pattern in Zaria - Ubogu, Andrew (Transport, 2008)
The concern over the likely impact of space‐adjusting technologies like telecommunications has attracted considerable attention in most studies. The focus of this paper is to examine how the proliferation of telecommunications affects intra‐urban flow of people in a medium size urban centre. This is with a view to understanding the implications of the use of Information and Communication Technology (ICT) on travel pattern in a sub‐Saharan urban centre like Zaria, Nigeria. In doing this however, attempts were made to answer the following questions: How have telecommunications substituted trip patterns in the study area? Does telecommunication usage eliminate all types of trips and to what extent has it helped to eliminate urban trips? In trying to provide answers to these questions, this study obtained purposive data from 335 telecommunication users that were carefully sampled. The results thereafter established that 76.7 % of the respondents substitute certain trips in the city and that telecommunications do not eliminate the physical movements of the residents surveyed. Furthermore, results also depict that not all trip types in the city are significantly substituted by telecommunications, rather the usage of ICT has tremendously helped to complement intra‐urban trip types in the city. The implications of these findings therefore are that with the improvement and subsequent increases in high tele‐density in the area, least‐cost travel planning will be ultimately achieved.First published online: 27 Oct 2010